Induced maturation and spawning of banana prawn, Penaeus merguiensis de Man, under captivity in the inshore waters of Karwar - Zacharia, Sherly; Kakati, V S (Indian Journal of Fisheries, 2011)
Investigations were made on the ovarian maturation of banana prawn (Penaeus merguiensis) held in a fixed hapa (2xlxlm) in inshore waters of Karwar bay. The shrimps collected (ablated females and males in the ratio 2:1) were subjected to experimental condition for a period of 10 days. The parameters such as salinity, temperature, pH and primary productivity of the seawater at the site were monitored regularly. Within 3-6 days after eyestalk ablation, 70% of the females matured in the cage and spawned successfully in situ, thereby indicating the possibility of induced ovarian maturation on commercial scale. Brood stock development on commercial scale for other important candidate species of aquaculture has been suggested.